Where is the ‘global’ in the European Union’s Health Research and Innovation Agenda? - Berner-Rodoreda, Astrid; Rehfuess, Eva; Klipstein-Grobusch, Kerstin; Cobelens, Frank; Raviglione, Mario; Flahault, Antoine; Casamitjana, Núria; Fröschl, Günter; Skordis-Worral, Jolene; Abubakar, Ibrahim; Ashrafian, Hutan; Agardh, Anette; et al. (BMJ global health, 2019)
Global Health has not featured as prominently in the European Union (EU) research agenda in recent years as it did in the first decade of the new millennium, and participation of low-income and middle-income countries (LMICs) in EU health research has declined substantially. The Horizon Europe Research and Innovation Framework adopted by the European Parliament in April 2019 for the period 2021-2027 will serve as an important funding instrument for health research, yet the proposed health research budget to be finalised towards the end of 2019 was reduced from 10% in the current framework, Horizon 2020, to 8% in Horizon Europe. Our analysis takes the evolvement of Horizon Europe from the initial framework of June 2018 to the framework agreed on in April 2019 into account. It shows that despite some improvements in terms of Global Health and reference to the Sustainable Development Goals, European industrial competitiveness continues to play a paramount role, with Global Health research needs and relevant health research for LMICs being only partially addressed. We argue that the globally interconnected nature of health and the transdisciplinary nature of health research need to be fully taken into account and acted on in the new European Research and Innovation Framework. A facilitated global research collaboration through Horizon Europe could ensure that Global Health innovations and solutions benefit all parts of the world including EU countries.